Application of Learning Using Chair Media To Improve Coordination of Basic Dribble Technique Skills In Basketball At SDN Bangkir (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is motivated by the suboptimal learning of basic dribbling techniques in basketball at SDN Bangkir. This study aims to improve students' coordination skills in performing basic dribbling techniques using chair media among fifth-grade students of class V-A at SDN Bangkir. This research was conducted at SDN Bangkir with the research sample population being the fifth-grade students of class V-A for the 2025/2026 academic year, consisting of 31 students, including 21 boys and 10 girls. The research method used is Classroom Action Research with a research design based on the Kemmis and McTaggart model, which focuses on cycles of reflection and continuous action. This research was conducted in three cycles. Each cycle consists of planning, action implementation, and observation. This classroom action research includes planning, action implementation, monitoring and evaluation, as well as analysis and reflection. Data collection is carried out at the monitoring and evaluation stage using student activity observation sheets and teacher activity sheets. Then the data were analyzed both quantitatively and qualitatively. The results of the first cycle of the study showed a completion rate of 16% or 5 students who had completed it. In the second cycle, there was a completion rate of 90% or 28 students who had completed it. Meanwhile, in cycle III, 100% or 30 people have achieved mastery. This shows that the actions taken in the first, second, and third cycles by both teachers and students can be said to have completed the learning process. Based on the above results, it can be concluded that using chair media can improve the basic dribbling technique coordination in basketball. From the research results, the researcher suggests that PJOK teachers should play a more active role during the implementation of teaching and learning activities so that students respond better and show more enthusiasm towards the provided lessons.